2021
DOI: 10.31284/j.iptek.2021.v25i1.963
|View full text |Cite
|
Sign up to set email alerts
|

Kontrol Kecepatan Motor BLDC dengan PID - Firefly

Abstract: Conventional DC motors often experience problems that require regular maintenance. The use of conventional DC motors can be replaced with Brushless DC (BLDC) motors. This BLDC motor has good efficiency and durability. Increasing the ability of BLDC motors can be done by speed regulation using the Proportional-Integral-Derivative (PID) method combined with Firefly Algorithm. Testing this method uses matlab 2014a. The firefly algorithm can obtain parameter values of Kp, Ki, and Kd which are then used as PID inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…[13]. In contrast, the black-box, or experimental approach, relies on input-output data of the system when there is no accessible physical insight [12], [14]. On the other hand, the gray-box model combines elements of both black-box and white-box modeling [15].…”
Section: Drive System Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13]. In contrast, the black-box, or experimental approach, relies on input-output data of the system when there is no accessible physical insight [12], [14]. On the other hand, the gray-box model combines elements of both black-box and white-box modeling [15].…”
Section: Drive System Modelsmentioning
confidence: 99%
“…Previous research utilizing PID methods has shown that the system exhibited significant steadystate error and overshoot, indicating the need for further improvement in control strategies to achieve better performance [12]. The primary objective is to minimize steady-state error and reduce overshooting in the operational performance of the motor.…”
Section: Introductionmentioning
confidence: 99%
“…Kemudi kereta otomatis tanpa awak, kecepatan operasi kereta, perjalanan kereta dengan Communications Base Train Control (CBTC) merupakan bentuk pengendalian dalam bidang transportasi [6]- [8]. Sistem kontrol dapat dimanfaatkan dalam operasi-operasi industri untuk mengendalikan kelembapan, waktu operasi, temperatur, kecepatan, monitoring aliran dalam proses, dan tekanan [1], [9], [10]. Pemanfaatan sistem kontrol yang baik dapat memberikan kemudahan dalam proses operasi, meningkatkan kualitas dan meminimalkan biaya produksi.…”
Section: Pendahuluanunclassified